Gain enhancement of dielectric resonator antenna for millimeter wave applications - Irfan Ali; Mohd Haizal Jamaluddin; M. R. Kamarudin; Abinash Gaya; M. H. Dahri (Universitas Ahmad Dahlan, 2019)
In this paper, dielectric resonator antenna (DRA) with enhanced gain operating on the higher order mode (????????????15???? ) is presented. The dielectric resonator antenna with dielectric constant ???????? of 10 and loss tangent of 0.002 is used. The DRA is fed by microstrip line through an aperture slot. The proposed antenna is designed at 26 GHz and achieved a gain of 7.9 dBi with corresponding simulated radiation efficiency of 93%. The impedance bandwidth of 1.5 GHz from 25.1 GHz to 26.6 GHz has been achieved. The reflection coefficient, antenna gain, radiation patterns, and efficiency of the antenna are studied. Simulations are performed using CST microwave studio, and their results are presented.